Pragmatics, semantics and the case of scalar implicatures - Reda, Salvatore Pistoia; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book is an advanced debate on the nature of scalar implicatures, one of the most popular topics in philosophical linguistics in the last 20 years. Leading theorists in the field offer an up-to-date presentation of the subject in a way that will help readers to orient themselves in the vast literature on the topic.
Keywords: Linguistics; Language and languages -- Philosophy; Psycholinguistics; Semantics; Pragmatics